Effect of temperature on sound transmission loss of laminated composite plate - Thanh, Pham Ngoc; Thinh, Tran Ich; Hien, Ta Thi (Vietnam Journal of Mechanics, 2022)
In this investigation, by an analytical approach, the influence of several key parameters, especially the temperature on the sound isolation capacity of the symmetrically finite orthotropic laminated composite plate is studied. The plate is modeled with classic thin-plate theory and is assumed to be simply supported on all four sides. The incident acoustic pressure is modeled as a harmonic plane wave impinging on the plate at an arbitrary angle. The sound transmission loss is calculated from the ratio of incident to transmitted acoustic powers